Immunohistochemical Testing of Conventional Adenomas for Loss of Expression of Mismatch Repair proteins in Lynch Syndrome Mutation Carriers: a Case Series from the Australasian Site of the Colon Cancer Family Registry - Walsh, Michael D (2012)
Debate continues as to the usefulness of assessing adenomas for loss of mismatch repair protein expression to identify individuals with suspected Lynch syndrome. We tested 109 polyps from 69 proven mutation carriers (35 females and 34 males) belonging to 49 Lynch syndrome families. All polyps were tested by immunohistochemistry for four mismatch repair proteins MLH1, MSH2, MSH6 and PMS2. Detailed pathology review was performed by specialist gastrointestinal pathologists. The majority of polyps (86%) were conventional adenomas (n = 94), with 65 tubular and 28 tubulovillous adenomas and a single villous adenoma. The remaining 15 lesions (14%) were serrated polyps. Overall, loss of mismatch repair expression was noted for 78/109 (72%) of polyps. Loss of mismatch repair expression was seen in 74 of 94 (79%) conventional adenomas, and 4/15 (27%) serrated polyps from mismatch repair gene mutation carriers. In all instances, loss of expression was consistent with the underlying germline mutation. mismatch repair protein expression was lost in 27 of 29 adenomas with a villous component compared with 47 of 65 adenomas without this feature (93% vs 73%; p=0.028). A strong trend was observed for high-grade dysplasia. mismatch repair deficiency was observed in 12 of 12 conventional adenomas with high-grade dysplasia compared with 60 of 79 with low grade dysplasia (100% vs 76%; p=0.065). We were unable to demonstrate a significant association between conventional adenoma size or site and mismatch repair deficiency. All (4/4 or 100%) of the serrated polyps demonstrating mismatch repair deficiency were traditional serrated adenomas from a single family. Diagnostic testing of adenomas in suspected Lynch syndrome families is a useful alternative in cases where cancers are unavailable. The overwhelming majority of conventional adenomas from mutation carriers show loss of mismatch repair protein expression concordant with the underlying germline mutation.